Solide en Gedegen Onderwijs. Wiskunde- en natuurkunde onderwijsdiscussies in de jaren 1920 als monitor voor disciplinevorming - Tompitak, Marco; Beckers, Danny (Studium, 2015)
Solid, high quality education. Debates on mathematics and physics education in the 1920s as monitor of discipline formationDutch secondary education in mathematics and physics during the first decades of the twentieth century offers a showcase in the growing apart of both the respective academic and teaching disciplines in these two subjects. Although there was one faculty of science at the universities, and all secondary school teachers were trained there both in mathematics and physics, there was a distinct feeling among teachers and academics that the two fields had grown apart.We illustrate this by investigating discussions among mathematics and physics teachers on both content and didactics of the curriculum. Mathematics had a clearly defined curriculum since 1863, mainly consisting of algebra and axiomatic Euclidean geometry. Supported by the fact that mathematics was regarded as the blissful road to certain knowledge and wisdom, this curriculum was fitted for up to eight hours per week. The physics curriculum had grown more organically; at the start of the new school system in the 1860s, secondary education in physics played a marginal role and was therefore endowed with only a few weekly lessons. By the 1920s, however, academic physics was highly regarded, and secondary education had grown both in enrolment and in its goals. Secondary education aimed no longer mainly to the preparation of the middle classes for their social function: it had also become a way of preparing for an academic or technical study.It turns out that mathematicians had much to lose in these developments and, in recognizing this fact, they stuck the more to old paradigms. In contrast, physics teachers and their academic colleagues were much more inclined to see opportunities in the changing educational environment. This is noticeable by diverging ideas about what ‘high quality’ education should be. Although mathematics had an old and highly regarded tradition in Dutch secondary education, early twentieth century discussions show that physics was gaining ground: both in a growing popularity of more intuitive ways of teaching physics – contrasting the formal Euclidean approach – and in a growing core physics curriculum.